Organic petrology and geochemistry of Early Permian shales from the Krishna‐Godavari Basin, India: Implications for Gondwana palaeoenvironment and climate. (5th September 2021) - Kala, Shubhangi; Devaraju, Javaregowda; Tiwari, Devleena Mani; Rasheed, Mohammed Abdul; Lakhan, Nongmaithem
Abstract : Lower Gondwana Kommugudem Formation of the Krishna‐Godavari (KG) Basin in the eastern coast of India records the deglaciation sequences of the Early Permian and is characterized by well‐preserved sandstone—shale—coal cyclothems. Kommugudem shales from six deep borewells of the KG Basin were studied for the organic petrological and geochemical compositions. The objective was to elucidate its source rock properties and depositional settings, which provide significant insights on the shifts in the Gondwanan palaeoenvironment and its climatic controls during the Early Permian. Maceral identification reveals the abundance of vitrinite that is distinctive to organic‐rich Permian Gondwana sediments. SiO2 enrichment with the dominance of quartz and clay minerals suggests moderate to strong weathering with palaeoclimate shift from cold, arid to hot, and semi‐arid during the Early Permian. The occurrence of higher short and mid‐chain alkanes with predominant n ‐C18 and important biomarker ratios suggest a transitional fluvio‐marine environment of deposition, which is also supported by the enrichment of redox‐sensitive trace elements. Prevailing anoxia enhanced the preservation of organic matter, despite reduced primary productivity, as indicated by low P/Ti ratios. A depleted δ 13 Corg (mean = −21.55‰) in the shales, distinct to the interglacial period, reflects the changes in p CO2 of the Early Permian atmosphere. Sedimentary biomarkers, carbon isotopes, and trace elements explicate the palaeoceanographic conditions and sea‐level changes, indicative of marine influence in the dominantly fluvial regime. The deposition and preservation of organic‐rich sediments under anoxic (possibly euxinic) water‐column took place, forming the prolific Pre‐trappean Lower Gondwana Kommugudem source rock in the KG Basin. Abstract : Geochemistry and organic petrography of Lower Gondwana shales from East coast, India. Elemental data indicates interglacial sequences with moderate‐strong weathering. Biomarkers and δ 13 Corg show marine influence in the fluvial dominated regime. Anoxia enhanced preservation of organic matter despite reduced productivity. Shift from cold arid to the semi‐arid post‐glacial warm climate in Upper Early Permian